Sifat Antirayap Ekstrak Kulit Bawang merah (Allium cepa L.) (Antitermites Properties of Onion Shell Extract) - Margaretha Uliartha Sari; Rudi Hartono; Luthfi Hakim (Program studi Kehutanan USU, 2013)
The aims of these researchs were to found the extract content of Allium cepa L., to evaluated weight lost of paper disc, to evaluated the toxicity level of Allium cepa L. extracts based on mortality rates and to evaluated feeding rate value. Research was done by extracting a sample with methanol then partitioning with n-Hexane. Extract with concentration of 2%, 4%, and 6% were used to test the toxicity of extract for Coptotermes curvignathus termites. The results showed extract content of Allium cepa L. was 16,62%. Termite mortality rate was 100% with concentration 2% and 4% on day 7th while the concentration of 6% on day 5th. So extract with the large concentration had higher mortality of termite than the lower. The weight lost of paper disc was around 3,72%–11,04% and feeding rate of termite was around 0,25 mg–0,73 mg. Keywords: extract of Allium cepa L., termite mortality, weight lost percentage, C. curvignathus